Does anyone need help out there? Lessons from designing online help. - Arnold JM; Csir F; Sias J; Zhang J (Internet Reference Services Quarterly, 2004)
In order to provide online help for distance students, as well as the increasing number of on campus students who regularly access library resources, a team of librarians from the Marshall University Libraries created an online library assistance site (HELP). This site brings together traditional print handouts, FAQs, online subject guides, course-specific guides, learning modules, and instructional videos in one central location where users can get assistance with library-related questions at their point of need. This article discusses the rationale for developing the site, the process of creating it and incorporating user input, ongoing content development, the impact upon the Libraries' Web site, and future development plans.